Analisis Tingkat Risiko Jeruk Siam di Desa Rantau Panjang Kecamatan Meurebo: Risk Level Analysis of Siamese Orange in Rantau Panjang Village Meurebo District - Nasution, Anisah; Murnisyati; Tanjung, Yulia Windi; Atikah, Qhisthina (Universitas Medan Area, 2025)
Siamese orange farming has high economic potential but also faces various risks that can affect farmers' productivity and income. This study aims to analyze the levels of production risk, price risk, and income risk. The research was conducted in Rantau Panjang Village, Meureubo District, West Aceh Regency, from October 2023 to June 2024. The sample was selected purposively (purposive sampling), as it is the only Siamese orange farming area in Meureubo District. Data were collected through interviews, documentation, and literature studies. The data analysis employed a quantitative approach using the coefficient of variation (CV), variance (S²), standard deviation (S), and lower bound (L). The results showed that the average income of Siamese orange farmers was IDR 11,596,167 per year. The risk analysis indicated that Siamese orange farming had a CV value of less than 0.5 and an L value greater than 0, suggesting that Siamese orange farming in Rantau Panjang Village remains profitable despite the risks faced by farmers.